Clean Air Learning Module for Grade Five Students: Modul Pembelajaran Udara Bersih untuk Siswa Kelas Lima - Nyugiantoro Nyugiantoro; Mahardika Darmawan Kusuma Wardana (Indonesian Journal of Education Methods Development, 2025)
General background: Teaching modules are essential learning tools in elementary classrooms because they provide structured content and guided exercises. Specific background: Many learning materials still lack engaging design and thematic integration needed for curriculum implementation, particularly for the topic “Clean Air for Health.” Knowledge gap: Limited studies describe the development of multi-subject thematic modules aligned with the Merdeka Belajar curriculum for grade five. Aims: This study presents the development of a teaching module on clean air designed to support thematic learning across civics, Indonesian language, science, social studies, mathematics, arts, and physical education. Results: The module consists of 49 pages containing explanations, illustrated stories, activities, and practice questions organized into three subthemes. The design process includes layout development using CorelDraw and content structuring based on competency mapping. Novelty: The module integrates multiple subjects in a visually appealing format that promotes student interest and supports curriculum alignment. Implications: This product can serve as a practical reference for teachers developing thematic learning materials in elementary schools. Highlights• Multi-subject thematic module• Clean air learning content• Curriculum-aligned design Keywords: Teaching Module, Thematic Learning, Elementary Education, Clean Air, Curriculum Design